INFORMATION INTEGRITY AND ELECTORAL CHOICES: UNDERSTANDING THE DYNAMIC OF NEWS, POLITICAL BRANDING, AND VOTING INTENTION - Anastasia Arini Ekaputri; Aldo Biondy Roesli; R Venesia Putri Maridjan; Evelyn Hendriana (Institute of Research and Community Outreach - Petra Christian University, 2025)
This study explores the relationship between news truthfulness, news credibility, source credibility, political brand trust, political brand image, and voting intention. The objective of this study is to understand how those factors collectively influence voters' perception and behavior. Using a quantitative approach, the data was collected through online surveys of 250 eligible voters in Indonesia, analyzed using Structural Equation Modeling (SEM). The results indicate that news truthfulness significantly increases both political brand trust and image. Meanwhile, source credibility positively influences trust, but does not notably affect brand image. Interestingly, news credibility increases political brand image without directly affecting trust. Furthermore, political brand image plays an important role in shaping voting intention, whereas political brand trust does not show a direct effect. By integrating those dimensions of political branding into one model, this study fills the gap in existing research and provides insights into the dynamics of voter behavior. This study suggests that political entities prioritize maintaining news truthfulness and the improvement of source credibility to build trust and create a positive brand image. Additionally political campaigns should adapt their communication strategies so that it is in line with the voter’s expectation in this complex media landscape for effective engagement and influence on electoral outcomes.